Community-based organisations and child well-being in sub-Saharan Africa: defining social change, effectiveness, and success. Issue 3 (3rd April 2023) - Wilkinson-Maposa, Susan; Shallwani, Sadaf; Kabati, Mary; Ndaiga, Prosper; Wame, Saeed; Zulu, Moses
ABSTRACT: International development agencies often support community-based organisations (CBOs) to improve the wellbeing of children and their families. The relevance, impact, and sustainability of these funding partnerships are neither widely nor consistently understood. This article discusses the CBO leader and practitioner perspective on social change and partnering. Surveys, interviews, and convenings involving CBOs from nine sub-Saharan African countries found that – distinct from international aid's focus on program implementation and service delivery, many CBOs focus on mobilising, engaging, and empowering the community to take charge of their own development. Donor–CBO partnering arrangements should integrate this role and definition of effectiveness.